Fixed Point Method to Analyze Differences between Hipparcos and ICRF2 - María José Martínez Usó; Francisco J. Marco Castillo; José Antonio López Ortí (Abstract and Applied Analysis)
From 1998, the International Astronomical Union (IAU) adopted a new Celestial Reference System: the International Celestial Reference System (ICRS). The first optical materialization was the Hipparcos catalogue, defining the Hipparcos Celestial Reference Frame (HCRF). The compilation of subsequent radio sources catalogues culminated in the current representation of the ICRF, the ICRF2 catalogue that is not sufficiently dense to cover all astrometrical purposes. Linking Hipparcos and ICRF2 is essential to uniformize the reference regardless of whether it is visible (HCRF) or not (ICRF). Many working groups provide their own complementary catalogs, some of whose sources are also in the ICRF2, with different reduction processes for positions. The point is that they provide information in more than one reference for a small number of objects. Some of these projects have been used by us to study the Hipparcos-ICRF2 differences: a certain number of couples of catalogs can be interrelated using a set of parameters. With these couples, we build a closed cycle with the same ending and departure couple. The parameters obtained from each couple affect the next; thus we have an iterative process whose fixed point is the solution that stabilizes it, providing a preliminary link for Hipparcos-ICRF2.